The solemn ode by Lomonosov and its interaction with rhetoric in Russian literature of 18th centure - Волик, Наталья Анатольевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
This article is about becoming of the solemn ode’s genre in Russian literature of 18th centure and about his interaction with the theoretical guidelines within the rhetorical culture. For this was conducted the structural and stylistical analysis of «The Ode on the day of accession of Elizabeth Petrovna by 1746». Then we compare ode and the genre of panegyric was described in «The Rhetoric» by Lomonosov. As a result solemn ode embodies era rhetorical model and is a sample of the finished word.